Adolescent boys' experiences of mental health and school health services - an interview study from Norway - Tonje Helland Lindborg; Inger Kristensson Hallström; Astrid Synnøve Litland; Helene Åvik Persson (BMC, 2024)
Abstract Background Mental health problems among adolescents is a global challenge. During the transition to adolescence, physiological, psychological, and social changes occur, leading to increased vulnerability. Thus, adolescent boys are less likely to seek help for mental health problems, which makes them an undetected group. The aim of this study was to gain a deeper understanding of adolescent boys' experiences of mental health and school health service. Methods An inductive, qualitative design was chosen using three focus group interviews and three individual interviews. The study included 18 adolescent boys in 7th grade, in a school located in a medium-sized municipality in Norway. The interviews were analysed with qualitative content analysis. The consolidated criteria for reporting qualitative research (COREQ) were followed in this study. Results The overall theme "barriers towards seeking help", and three categories- navigating stigma and privacy concerns; perceptions of self-responsibility; and lacking knowledge of mental health problems and help-seeking-described the adolescent boys experiences. The awareness and willingness to seek help were present, but there are barriers preventing the adolescent boys from acting on that willingness. Conclusions Lack of knowledge and a non-permissive culture for mental health problems among adolescents contributes to decreased help-seeking behaviour among adolescent boys. The school health service is the most related health service for adolescents and should focus on being available and strengthening empowerment and mental health literacy through the development and implementation of interventions to promote mental health.